Obesity and mental health issues among healthcare workers: a cross-sectional study in Sabah, Malaysia - Narinderjeet Kaur Dadar Singh; Jiann Lin Loo; Azlan Ming Naing Ko; Syed Shajee Husain; Jiloris Frederick Dony; Syed Sharizman Syed Abdul Rahim (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - This study aims to determine the prevalence of obesity and its relationship with mental health issues among healthcare workers in Kota Kinabalu District Health Office, Sabah Borneo and its associating factors. Design/methodology/approach - This cross-sectional study was conducted among 387 healthcare workers working in the Kota Kinabalu District Health Office, Sabah. Sociodemographic data and anthropometric measurements were collected and DASS 21 questionnaire was used to assess mental health status. Findings - The prevalence of obesity among healthcare workers was 29%, which is significantly associated with years of service (p = 0.016) and abnormal depression subscale scores (p = 0.012) at univariate analysis. The percentage of abnormal subscale score for depression, anxiety and stress was 16, 26 and 12%, respectively. Multivariable logistic regression revealed that more than five years of service years (OR 2.23, 95%CI 1.16-4.28) and high depressive subscale score (OR 2.09, 95%CI 1.18-3.71) were both significantly associated with obesity. Originality/value - This study has affirmed the link between physical and mental health. Policies that tackle both issues should be put in place to promote wellness among healthcare workers.